Correlation between Epicardial Fat Thickness and Clinical and Anthropometric Variables in an Elderly Population - Castanheira,Joaquim (2021)
Abstract Background Epicardial fat (EF) thickness is a marker of visceral adiposity and consequently considered an important predictive marker of cardiovascular and metabolic risk. Objective To describe echocardiographic features of the heart in an elderly population and to study the correlation between EF thickness and clinical and anthropometric variables. Methods A sample of 34 individuals (25 women) aged between 65 and 92 years, who attended a private institution in the central region of Continental Portugal, was analyzed. A standardized sociodemographic questionnaire was applied, and anthropometric assessment, echocardiography and blood pressure measurement were performed in all subjects. A correlational analysis of EF thickness with anthropometric and clinical parameters was performed. The association between variables was tested by Pearson's correlation and point-biserial correlation. A value of p < 0.05 was defined as statistically significant. Results EF thickness was higher in males (6.0 ± 1.4 mm vs 5.2 ± 0.9 mm in females), and ranged from 4 to 9 mm. There were statistically significant correlations between EF thickness and weight (r = 0.4; p = 0.02), body surface area (r = 0.4; p = 0.02), lean mass (r = 0.4; p = 0.03), calf circumference (r = 0.5; p = 0.01) and left ventricular end-diastolic diameter (r = 0.3; p = 0.04). Conclusion EF thickness was higher in males and was significantly correlated with anthropometric parameters of adiposity and left ventricular end-diastolic diameter. Int J Cardiovasc Sci. 2020; [online].ahead print, PP.0-0